Increased Accumulation and Retention of rhFVIIa (eptacog beta) in Knee Joints of Hemophilia A Mice Compared to Wild-Type Mice - Magisetty, Jhansi; Pendurthi, Usha R.; Madhunapantula, SubbaRao V.; Grandoni, Jerry; Rao, L. Vijaya Mohan (Thrombosis and Haemostasis, 2019)
Our earlier studies showed that recombinant human factor VIIa (rhFVIIa) administered intravascularly in mice disappeared rapidly from the circulation. However, a small fraction of rhFVIIa that entered extravascular remained functionally active for an extended period. The present study aims to investigate the dose-dependency of rhFVIIa accumulation and retention in mouse knee joints and test whether the hemophilic condition affects rhFVIIa sequestration in joints. Wild-type and FVIII−/− mice were injected with three doses of rhFVIIa (eptacog beta, 90, 250, and 500 μg/kg) via the tail vein. At varying times following rhFVIIa administration, blood and knee joints were collected to measure FVIIa activity and antigen levels in plasma and joint tissues. Joint tissue sections were analyzed by immunohistochemistry for the presence of rhFVIIa. Vascular permeability was assessed by either Evans Blue dye or fluorescein dextran extravasation. The study showed that rhFVIIa accumulated in knee joints of wild-type and FVIII−/− mice in a dose-dependent manner. rhFVIIa antigen and FVIIa activity could be detectable in joints for at least 7 days. Significantly higher levels of rhFVIIa accumulation were observed in knee joints of FVIII−/− mice compared with that of wild-type mice. Immunohistochemical analyses confirmed higher levels of rhFVIIa retention in FVIII−/− mice compared with wild-type mice. Additional studies showed that FVIII−/− mice were more permissible to vascular leakage. In conclusion, the present data demonstrate a dose-dependent accumulation of rhFVIIa in knee joints, and the hemophilic condition enhances the entry of rhFVIIa from circulation to the extravascular. The present data will be useful in improving rhFVIIa prophylaxis.
Keywords: factor VIIa; eptacog beta; hemophilia; permeability; prophylaxis